Exploring the role of orbital exenteration in survival among patients with severe rhino-orbital cerebral mucormycosis: a case series - Davuluru, Shaili S.; Clark, Andrew J.; Cahill, Kenneth; Foster, Jill A.; Zhang-Nunes, Sandy (Frontiers in Ophthalmology, 2025)
Rhino-orbital cerebral mucormycosis (ROCM) is a rare, but potentially fatal opportunistic infection due to a fungus of the Mucorales sp. that involves infiltration of the sinuses, orbits, and central nervous system. Orbital exenteration (OE) is reserved for severe cases refractory to initial antifungal treatment and endoscopic sinus debridement, though there is currently no consensus on the ideal timing of OE and its impact on infection progression and survival. In this case series, we present three cases of similar, extensive ROCM that were candidates for OE after initial medical and surgical management with variable outcomes. We discuss that undergoing OE does not necessarily correlate with survival after ROCM infection and that the decision to proceed with exenteration should be personalized based on the status of a patient's comorbidities and the nature and extent of infectious spread. Globe-sparing OE may serve as a viable alternative for patients with localized, late-stage infection or reversible ROCM risk factors given vision preservation and less postoperative disfigurement with possibly comparable efficacy.